ISU KRITIS PEMBELAJARAN ANAK USIA DINI - Dwi Istati Rahayu; Fitria Rahmawati (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2020)
Early childhood is the golden age, where at this time the potential for development in all its aspects is so fast, so that at this time it is suspected as the founder of character, intelligence, and skills until he is an adult. Facing this period, stimulation of all aspects of development must continue to be considered, so that children's development becomes optimal. The principle of providing stimulation to children's development is learning through play. This descriptive research was conducted in the city of Mataram, with a sample of 8 institutions, consisting of PAUD. Collecting data using observation techniques, in-depth interviews, and documentation. Data analysis uses data reduction, data presentation, as well as conclusions and verification. The results of the study indicate that the issues critical to learning in PAUD include learning that prioritizes the development of abilities alone, such as the ability to read, write and count; imbalance of stimulation of the ability of the right and left hemispheres of the brain; the use of learning media in PAUD institutions is minimalistic; learning activities in PAUD institutions that are more dominant are classical; the grouping of children in PAUD institutions is carried out based on their age level and not based on existing abilities or developmental achievements. These problems have been around for a long time, and are difficult to fix. Barriers to eliminating this problem come from the child's parents, teachers, PAUD regulations, and limited infrastructure.